If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 2x + -3 Reorder the terms: -4 + 9x = 2x + -3 Reorder the terms: -4 + 9x = -3 + 2x Solving -4 + 9x = -3 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -4 + 9x + -2x = -3 + 2x + -2x Combine like terms: 9x + -2x = 7x -4 + 7x = -3 + 2x + -2x Combine like terms: 2x + -2x = 0 -4 + 7x = -3 + 0 -4 + 7x = -3 Add '4' to each side of the equation. -4 + 4 + 7x = -3 + 4 Combine like terms: -4 + 4 = 0 0 + 7x = -3 + 4 7x = -3 + 4 Combine like terms: -3 + 4 = 1 7x = 1 Divide each side by '7'. x = 0.1428571429 Simplifying x = 0.1428571429
| 8b+6(-6-2b)=4+b | | x-5+x-5+x-5+x-5=12+x+x | | 2x-3=2(x+4) | | 18(w+3)-45=18+54 | | 25-7a=28+4a | | 5x^4-30x^2= | | 32=5-4a-5a | | 0.02(y-9)+0.20y=0.16y-0.6 | | 2(9s+7)-10s=2(4s+2)-8 | | 18-2x=-36 | | 5w-6+3w=-12 | | -4-3x=17 | | 4+3-939340823094+6-x=-34 | | (5x^2y-2xy^2+3xy-5)(-2x^2y-3xy^2+4xy+7)= | | -4(3x-2)=2x+17 | | 4x/20+10=2x-26 | | 6x+4y=-24 | | 2y-8=6y | | 9x-4=x-3 | | 2+6x+5x=-130 | | 4(x-2)=4(x-3) | | 6t+20=9t+20 | | -58-4x=17+x | | 0.50x+0.45(30)=36.5 | | (3+x)2=x+2 | | 15y-6-10y=9 | | 25(10-x)=25x+250 | | 2y+-4y+y=40 | | 1.5t^2+12t-52=0 | | 7-4(5+x)=3x-7(2x-1) | | 24-2s=2-(2s-3) | | 7x+1=10x-50 |